Pengaruh Think Pair and Share terhadap Keterampilan Berbicara Mahasiswa - Amir, Johar; Suhartina, Suhartina (IAIN Parepare, 2023)
The aim of this study is to describe the influence of think pair and share on the confidence and value of speaking skills of students of HTN Class B. The method used in this research is the method of quantitative research. The population in this study was 33 students of Prodi HTN class B, while the sample in this research was 33 people using the sampling technique of saturated samples, which means the entire population is sampled. Self-confidence instrument using a lift. The results of the study show that statistical testing with simple linear regression, suggests that the TPS model can improve student self-confidence. The test results prove of student confidence attitudes are positively and significantly influenced by TPS learning model.